Gulf of Lampung Bamboo Fixed Net Cages Structural Design Identification - Shila Atika Sari; Mochammad Fathurridho Hermanto; Elsa Rizkiya Kencana; Nafisa Nandalianadhira (International Journal of Offshore and Coastal Engineering, 2024)
Renewable materials are being discussed and researched more recently. One renewable source of material is plants, either with a long life like wood or a short life like bamboo. In Indonesia, bamboo is widely used also for the structures of fixed net cages. This research aims to analyze the structure of the fixed bamboo net cage installed in the waters of Gulf Lampung. The analysis used in this paper is in place. The in-place analysis will give the unity check and deflection result due to load combined by the standard BKI Guidelines for Aquaculture. Based on the results, the structure has met the standard in operation conditions with the maximum unity check value of 0.52 on the group pile. Nevertheless, the largest unity check value of 1.20 on group piles in storm conditions is due to increased lateral loading. The result of deflection already has good serviceability, with a maximum horizontal deflection value occurring in storm conditions of 0.58 cm and a maximum vertical deflection in operation conditions of 0.89 cm. The structure of the fixed net cages has yet to meet the requirements during storm conditions by unity check.